EXPRESSION OF HABIBURRAHMAN EL SHIRAZY'S PROFESSION IN THE NOVELETTE IN MIHRAB CINTA - Juni Syaputra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this research is to know how far the expression of profession Habiburrahmn El Shirazy in novelet Dalam Mihrab Cinta. The method used in this research is descriptive method, this research data is the profession element contained in novelet In Mihrab Cinta. Technique of collecting data in this research is by using table data of element of profession of author in novelet. Data analysis techniques by reading the whole novelet, marking the parts of the profession, then the data found included into the list of data types of professions. The results show that the profession of Habiburrahman El Shirazy undertaken by the character of Syamsul in novelet Dalam Mihrab Cinta has the same profession that is owned as a lecturer, a teacher or lecturer, writer/author, and boarding school. Professions occupied by Habiburrahman El Shirazy is a profession-profession that is able to provide a more decent life for himself and family. Thus, Habiburrahman El Shirazy belongs to a person who has extraordinary professions in running and organizing his life.